Vegetable growers of BRAC and Flood 1998: a case study of Sonaidanga Balkuntthapur VO - Ahmed, Dilruba (BRAC Research and Evaluation Division (RED), 2019)
This study was conducted to know how the flood of 1998 affected the vegetable production of BRAG members and how they copped with the situation. The observation was conducted on 6 members of Sonaidanga Baikuntthapur VO in Gaibandha. On average they used 30.2 decimals of land for vegetable cultivation. Vegetable cultivation was an important source of income for the households. Due to flood the vegetable plots went under about 137 centimetre deep water. On average they lost Tk. 3, 188 due to the damage of thejr vegetable crops caused by flood. It seriously affected their regular income flow, thus their normal life. To cope with the situation they took some measures such as disposing of savings, starting of new business, taking of loan, reducing household consumption and expenditure, and selling of stored paddy. In order to make up the losses members needed new loans from BRAG for vegetable cultivation after flood.